Al-Tahlil al-Dilaly wa Tathbiq al-Tarbawi Lima’na Kalimah Mubarak fi al–Qur’an al-Karim ‘ala Manzhuri Toshihiko Izutsu - Khusnul Mubarok; Muhammad Fadhil Hadziq; Abd Rofi Fathoni Nidhomillah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Semantics, a branch of linguistics, studies meaning in language by analyzing how words and sentences convey meaning in the context of communication. This study aims to use a semantic approach to understand how meaning is formed and interpreted in the Qur'ān. The main objective is to analyze the meaning of the word